PET/CT in Lung Cancer (PET/CT,, 2018)
This concise, excellently illustrated pocket book provides an up-to-date summary of the science and practice of PET/CT imaging in lung cancer. The coverage encompasses the entire spectrum of lung cancer - pathology, radiological and PET/CT imaging, and management. Readers will also find information on the physics of PET and its use in respiratory gating and radiotherapy planning. The highlights of the book are the exquisite depiction of normal variants, pitfalls, and artifacts and a pictorial atlas of the various types of lung cancer and their manifestations. The contributing authors are well-known and experienced oncologists, pathologists, radiologists, and nuclear physicians. This book has been compiled under the auspices of the British Nuclear Medicine Society. It will be of high value for nuclear physicians, radiologists, referring clinicians and oncologists, and paramedical staff working in these fields.